2008
DOI: 10.1063/1.2996581
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial ferromagnetic Fe3Si∕Si(111) structures with high-quality heterointerfaces

Abstract: To develop silicon-based spintronic devices, we have explored high-quality ferromagnetic Fe3Si/silicon (Si) structures. Using low-temperature molecular beam epitaxy at 130 • C, we realize epitaxial growth of ferromagnetic Fe3Si layers on Si (111) with keeping an abrupt interface, and the grown Fe3Si layer has the ordered DO3 phase. Measurements of magnetic and electrical properties for the Fe3Si/Si(111) yield a magnetic moment of ∼ 3.16 µB/f.u. at room temperature and a rectifying Schottky-diode behavior with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
119
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(128 citation statements)
references
References 22 publications
8
119
1
Order By: Relevance
“…[9,10] By low-temperature molecular beam epitaxy (LTMBE), we recently demonstrated highly epitaxial growth of a binary Heusler alloy Fe 3 Si on Si and obtained an atomically abrupt heterointerface. [11] In this letter, inserting a heavily doped n + -Si layer near the abrupt interface between Fe 3 Si and n-Si, we achieve an effective Shottky tunnel barrier for spin injection into Si. Using nonlocal signal measurements, we demonstrate electrical injection and detection of spin-polarized electrons in Si conduction channels though the Schottky-tunnel-barrier contacts.…”
mentioning
confidence: 99%
“…[9,10] By low-temperature molecular beam epitaxy (LTMBE), we recently demonstrated highly epitaxial growth of a binary Heusler alloy Fe 3 Si on Si and obtained an atomically abrupt heterointerface. [11] In this letter, inserting a heavily doped n + -Si layer near the abrupt interface between Fe 3 Si and n-Si, we achieve an effective Shottky tunnel barrier for spin injection into Si. Using nonlocal signal measurements, we demonstrate electrical injection and detection of spin-polarized electrons in Si conduction channels though the Schottky-tunnel-barrier contacts.…”
mentioning
confidence: 99%
“…In recent years, several studies have been performed on epitaxial growth of FM metal thin film on III-V and IV group SCs. [2][3][4][5][6][7] For such type of devices, transition metals and their alloys are of great interest. Among various types of transition metals and alloys, CoFe magnetic alloy is of interest due to its soft magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we focus on single-crystal Fe 3 Si, which has desirable properties such as a smaller damping constant and a larger resistivity than those for Ni 80 Fe 20 (Py), the most commonly used spin source. 19 Moreover, high-quality single-crystal Fe 3 Si can be easily grown on semiconducting substrates such as Si, Ge and GaAs with atomically flat interfaces. [19][20][21] This means that Fe 3 Si can be applied to a wide variety of materials, allowing the development of novel semiconductor-based spintronic devices in addition to metal-based devices.…”
mentioning
confidence: 99%
“…19 Moreover, high-quality single-crystal Fe 3 Si can be easily grown on semiconducting substrates such as Si, Ge and GaAs with atomically flat interfaces. [19][20][21] This means that Fe 3 Si can be applied to a wide variety of materials, allowing the development of novel semiconductor-based spintronic devices in addition to metal-based devices. In the present study, a significant enhancement of spin-injection efficiency is demonstrated by using a single-crystal Fe 3 Si layer.…”
mentioning
confidence: 99%
See 1 more Smart Citation